2011
DOI: 10.1021/la104840c
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Functionalizable, Nanometer-Thick Poly(acrylic acid) Films Spontaneously Assembled on Oxidized Aluminum Substrates: Structures and Chemical Properties

Abstract: Immersion of oxidized aluminum substrates in ethanol solutions of poly(acrylic acid) (PAA), followed by extensive solvent immersion, results in tenaciously chemisorbed, nanometer scale, controllable thickness films for a wide range of solution concentrations and molecular weights. Atomic force microscope images reveal isolated polymer globules from adsorption in low-concentration solutions with crossover to conformal, highly uniform, nanometer-thickness films at higher concentrations, an indication that the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The manufacturer of the polymer used in this work states that only benzene could occur as an impurity with a concentration smaller than 0.1%. Due to this knowledge about the polymer impurity and since it is known that surface carbon contamination is typically removed during the PAA deposition process 29 31 39 40 , we attribute this extra intensity to aliphatic adventitious carbon on top of the polymer film. It was estimated by Koo et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer of the polymer used in this work states that only benzene could occur as an impurity with a concentration smaller than 0.1%. Due to this knowledge about the polymer impurity and since it is known that surface carbon contamination is typically removed during the PAA deposition process 29 31 39 40 , we attribute this extra intensity to aliphatic adventitious carbon on top of the polymer film. It was estimated by Koo et al .…”
Section: Resultsmentioning
confidence: 99%
“…It was estimated by Koo et al . that the coverage of ambient-borne contaminants ranged between 5–10% of the uncoated substrate and it was observed that this contamination was rapidly displaced by polymer molecules at the aluminum oxide surface by immersion in the PAA solution 40 . Since this is a small contribution to the surface species and is not primarily located at the polymer/oxide interface, we assume that the effects of adventitious carbon on the interface chemistry are negligible.…”
Section: Resultsmentioning
confidence: 99%
“…This estimation corresponds well with previous work. [8,42] When looking at the fitted values of the constant phase element (CPE) of the oxide layer (Q 2 ), a value around 100 ± 2.2 µF/cm 2 is obtained. If an assumption of the dielectric constant ( ) for aluminum oxide is taken to be 9.1, then a thickness estimation of 2, 9 ± 0.1 nm is retrieved.…”
Section: Proposed Electrical Equivalent Circuit (Eec) To Describe the Paa/aluminummentioning
confidence: 99%
“…[3][4][5][6][7] These diluted polymer solutions mainly consist of organic solvents and for acrylic polymers, this is commonly an alcohol. 8 Fowkes et al and Abel et al previously have shown that the nature of the solvent has an influence on the amount of polymer deposited on the substrate surface and that the solvent's acid-base properties govern the adsorption process in general. 9,10 But despite the large abundance of the solvent molecules in contact with the oxide surface, the influence of the solvent itself on the oxide chemistry is often neglected.…”
Section: Atr-ftir Kretschmann Setup Introductionmentioning
confidence: 99%